Input matching, error augmentation, self-tuning, and output error identification: Algorithmic similarities in discrete adaptive model following - Johnson, C. (IEEE transactions on automatic control, 1980)
Four distinct approaches to adaptive controller formulation are applied to a linear discrete plant in an attempt to implement adaptive model following. Surprisingiy, each of the four resulting controllers proves reducible to the same basic algorithm. The details of this reduction are given to pinpoint the similarities of the products of these dissimilar strategies and to provide a basis for future examination of their differences in more complex applications.